2013
DOI: 10.1134/s0362119713070074
|View full text |Cite
|
Sign up to set email alerts
|

From the flight of Yu.A. Gagarin to the contemporary piloted space flights and exploration missions

Abstract: The first human flight to space performed by Yu.A. Gagarin on April 12, 1961 was a crucial event in the history of cosmonautics that had a tremendous effect on the further progress of human civilization. Gagarin's flight had been preceded by targeted biomedical research with the use of diverse biological objects on board rockets and artificial satellites. This research led to the conclusion on the fundamental possibility for humans to fly in space. After a series of early flights and improvements in the medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Investigations of weightlessness effects on living organisms began with the launch of dog Laika to space in 1957 and the flight of Yuri Gagarin in 1961. Since then, studies in the domain of space medicine have revealed a variety of spaceflight effects on human cardiovascular, neurovestibular, and musculoskeletal systems (Grigoriev and Potapov, 2013). The hypogravity motor syndrome (HMS) is considered to be a severe microgravity effect on astronauts (Grigoriev and Kozlovskaya, 1991), which is why success of future remote space missions will be highly dependent on how soon we get to the roots of HMS pathogenesis and be ready to offer methods of prevention on the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of weightlessness effects on living organisms began with the launch of dog Laika to space in 1957 and the flight of Yuri Gagarin in 1961. Since then, studies in the domain of space medicine have revealed a variety of spaceflight effects on human cardiovascular, neurovestibular, and musculoskeletal systems (Grigoriev and Potapov, 2013). The hypogravity motor syndrome (HMS) is considered to be a severe microgravity effect on astronauts (Grigoriev and Kozlovskaya, 1991), which is why success of future remote space missions will be highly dependent on how soon we get to the roots of HMS pathogenesis and be ready to offer methods of prevention on the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…This is illustrated by the intense development of projects related to the possibility of manned flights to Mars, which seems to be of the high est scientific interest among the planets of the Solar System. Surely, manned flights to Mars require the solution of a set of problems related to the preservation of the health and working capacity of the crew at all stages of the mission and after its termination [1][2][3][4]. Disorder of the immune system, which is one of the key integrative and regulatory systems of the human body, aimed at preserving and maintaining its genetic homeo stasis, is among the factors that may limit an increase in the duration of a human's stay under the conditions of a space flight.…”
mentioning
confidence: 99%
“…This is achieved through the use of preventive measures, proper regimens of work and leisure, psychological support, comprehensive medical support in flight, and postflight rehabilitation activities [4]. However, immunological studies conducted over the last few decades indicate that adaptation of the human immune system to a space flight is achieved at the cost of a significant increase in the tension of the immune system.…”
mentioning
confidence: 99%